MIRRORS AND WINDOWS: Sociocultural Studies of Human-Animal Relationships - Mullin, Molly H (Annual review of anthropology, 1999)
Humans' relationships with animals, increasingly the subject of controversy, have long been of interest to those whose primary aim has been the better understanding of humans' relationships with other humans. Since this topic was last reviewed here, human-animal relationships have undergone considerable reexamination, reflecting key trends in the history of social analysis, including concerns with connections between anthropology and colonialism and with the construction of race, class, and gender identities. There have been many attempts to integrate structuralist or symbolic approaches with those focused on environmental, political, and economic dimensions. Human-animal relationships are now much more likely to be considered in dynamic terms, and consequently, there has been much interdisciplinary exchange between anthropologists and historians. Some research directly engages moral and political concerns about animals, but it is likely that sociocultural research on human-animal relationships will continue to be as much, if not more, about humans.